Kenya National Adaptation Process Meeting - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The first National Adaptation Planning (NAP) Meeting in 2014 took place on February 10th at the Sarova Panafric Hotel in Nairobi, bringing together key stakeholders in the agriculture sector. The meeting was geared at taking forward the implementation of agricultural priority actions in the National Climate Change Action Plan (NCCAP) 2013 – 2017. Photos: S.Kilungu ( CCAFS)